Beispiel Nr: 21
$\text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2 x -7 y =-8\\ 7 x -1 y = -9 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 2 x -7 y =-8\\ II \qquad 7 x -1 y = -9 \\ I \qquad 2 x -7 y =-8 \qquad / \cdot7\\ II \qquad 7 x -1 y = -9 \qquad / \cdot\left(-2\right)\\ I \qquad 14 x -49 y =-56\\ II \qquad -14 x +2 y = 18 \\ \text{I + II}\\ I \qquad 14 x -14 x-49 y +2 y =-56 +18\\ -47 y = -38 \qquad /:\left(-47\right) \\ y = \frac{-38}{-47} \\ y=\frac{38}{47} \\ \text{y in I}\\ I \qquad 2 x -7\cdot \frac{38}{47} =-8 \\ 2 x -5\frac{31}{47} =-8 \qquad / +5\frac{31}{47} \\ 2 x =-8 +5\frac{31}{47} \\ 2 x =-2\frac{16}{47} \qquad / :2 \\ x = \frac{-2\frac{16}{47}}{2} \\ x=-1\frac{8}{47} \\ L=\{-1\frac{8}{47}/\frac{38}{47}\} \end{array} & \begin{array}{l} \\I \qquad 2 x -7 y =-8\\ II \qquad 7 x -1 y = -9 \\ I \qquad 2 x -7 y =-8 \qquad / \cdot\left(-1\right)\\ II \qquad 7 x -1 y = -9 \qquad / \cdot7\\ I \qquad -2 x +7 y =8\\ II \qquad 49 x -7 y = -63 \\ \text{I + II}\\ I \qquad -2 x +49 x+7 y -7 y =8 -63\\ 47 x = -55 \qquad /:47 \\ x = \frac{-55}{47} \\ x=-1\frac{8}{47} \\ \text{x in I}\\ I \qquad 2 \cdot \left(-1\frac{8}{47}\right) -7y =-8 \\ -7 y -2\frac{16}{47} =-8 \qquad / +2\frac{16}{47} \\ -7 y =-8 +2\frac{16}{47} \\ -7 y =-5\frac{31}{47} \qquad / :\left(-7\right) \\ y = \frac{-5\frac{31}{47}}{-7} \\ y=\frac{38}{47} \\ L=\{-1\frac{8}{47}/\frac{38}{47}\} \end{array} \end{array}$